The crime of forced theft in Libyan legislation (Journal of Human Sciences, 2022)
This research dealt with the crime of forced robbery in the Libyan legislation, where serious crimes are considered among the problems facing human societies, as they threaten security and societal stability because they combine assault on money and assault on oneself at the same time, especially in light of the current circumstances that are characterized by violence and armed robbery. And robbery by force of arms, as some of them were associated with murder, where the research aimed to know the plan of the Libyan legislator in the place of criminal protection regarding the seizure of movable money owned by others by coercion and what is the punishment approved by the Libyan legislator to ensure the security and stability of society.